UJI EFEKTIVITAS SALEP EKSTRAK HERBA PEGAGAN (Centella asiatica (L.) Urban) TERHADAP LUKA BEDAH PADA TIKUS - Zuniarto, Ahmad Azrul; Fauzia, Rizki Rahmah (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2017)
Background: Pegagan (Centella asiatica (L.) Urban) has been studied that has good wound healing activity in surgical wound with stimulating collagen synthesis, increasing collagen secretion, stimulating fibroblast proliferation, antibacterial activity and antioxidants. Objective: To determine the effectiveness of Pegagan herb extract (Centella asiatica (L.) Urban) in healing of surgical wound in male white rat and to determine the concentration of Pegagan herb extract (Centella asiatica (L.) Urban) which is most effective against wound healing surgery in male white rat. Method: The method used experimental study. The experimental animals were divided into 5 groups, which are group X1 was the test group with Pegagan herb extract concentration of 2,5%, group X2 was the test group with Pegagan herb extract concentration of 5%, group X3 was the test group with Pegagan herb extract concentration of 10%, group K (+) was the test group with positive control, and group K (-) was the test group with negative control. Results: The results showed that the ointment of Pegagan extract with concentrations of 5% and 10% could heal the wound better than the positive control. Oinment of Pegagan extract with concentration of 2,5% had not significant difference compared with positive control (povidone iodine). Conclusion: Administration of oinment of Pegagan herb extract (Centella asiatica (L.) Urban) with concentration of 2.5%, 5%, and 10% were effective in healing of surgical wound in male white rat.